PENGARUH PENGEMBANGAN KARIR, MOTIVASI INTRINSIK DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA KANTOR DINAS KEBUDAYAN DAERAH ISTIMEWA YOGYAKARTA - Arsenius Agung Hambut; Prayekti - (Universitas Bina Taruna Gorontalo, 2023)
This study aims to determine the effect of career development, intrinsic motivation and organizational culture on employee job satisfaction at the Yogyakarta Special Region Culture Office. The population of this study were 55 employees of the Yogyakarta Special Region Cultural Service Office. The sampling technique is a saturated sample or census by taking a sample of 55 employees. Data collection methods with questionnaires. Data analysis used is multiple linear regression analysis. The results of this study indicate that there is a positive and significant effect of Career Development variables on Employee Job Satisfaction, a positive and significant effect of Intrinsic Motivation variables on Employee Job Satisfaction and a positive and significant effect of Organizational Culture variables on Employee Job Satisfaction.